1991
DOI: 10.1128/iai.59.9.3227-3236.1991
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an intracellular bacterium from hamsters (Mesocricetus auratus) with proliferative ileitis and reproduction of the disease with a pure culture

Abstract: An intracellular bacterium was isolated from hamsters (Mesocricetus auratus) with proliferative ileitis. The organism was isolated in Intestine 407 and GPC-16 cell cultures (incubated in a microaerophilic atmosphere) from isolated and lysed epithelial cells from hamsters with proliferative ileitis. The bacterium measured 1.4 to 1.7 jim in length by 0.26 to 0.34 jim in width, was slightly curved, and had an irregular trilaminar cell wall. Inoculation of hamsters with a cell culture lysate containing the organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 11 publications
(15 reference statements)
2
15
0
Order By: Relevance
“…Previous reports had indicated that this newly recognized organism was the intracellular bacterium present in lesions in the natural disease (7,16), but this report establishes its etiologic role in the disease. Similar results have been reported in proliferative enteritis in hamsters (24), but that report did not identify the agent used, and a subsequent report indicated that their cell cultures were contaminated by a Chlamydia species (25).…”
Section: Discussionsupporting
confidence: 64%
“…Previous reports had indicated that this newly recognized organism was the intracellular bacterium present in lesions in the natural disease (7,16), but this report establishes its etiologic role in the disease. Similar results have been reported in proliferative enteritis in hamsters (24), but that report did not identify the agent used, and a subsequent report indicated that their cell cultures were contaminated by a Chlamydia species (25).…”
Section: Discussionsupporting
confidence: 64%
“…However, an antigenically and morphologically similar bacterium is found within the enterocytes of hamsters (Mesocricetus auratus) with PE (11) and has been cultivated in tissue culture. Pure cultures of that organism have transmitted PE in hamsters (20). The intracellular bacterium of swine, formerly known as a Campylobacter-like organism, has been given the vernacular name ileal symbiont intracellularis (IS-intracellularis) (5).…”
mentioning
confidence: 99%
“…Macroscopically, this complex of diseases is characterized by distention of the ileal wall and microscopically by proliferation of the ileal epithelium and lymphatic tissue of the mucosa and submucosa with hypertrophy of the muscular layers. Proliferative ileitis (transmissible ileal hyperplasia, wet tail) has been reported in hamsters and is characterized by hyperplasia of the ileal epithelium and pyogranulomatous inflammation [29]. Recently, adenocarcinoma of the cecum with Crohn-like features was reported in baboons [27].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Campylobacter-like organisms have been observed in hamsters with proliferative ileitis using transmission electron microscopy and Warthin-Starry staining [7]. Recently, it has been possible to isolate the bacterium using cell cultures, reproduce the disease following oral inoculation of hamsters with the organism, and reisolate the organism, essentially satisfying Koch's postulates [29]. Lack of cross-reactivity of rabbit antibodies specific for members of the genus Campylobacter (C. jejuni, C. hyointestinalis and C. coli) suggests that this organism is antigenically distinct and probably not a member of the genus Campylobacter [29].…”
Section: Discussionmentioning
confidence: 99%